Zeldovich and the Missing Baryons, Results from Gravitational Lensing. Issue Volume 11:Issue S308(2015) (12th October 2016) - Schild, Rudolph E.
Abstract: Central to Zeldovich's attempts to understand the origin of cosmological structure was his exploration of the fluid dynamical effects in the primordial gas, and how the baryonic dark matter formed. Unfortunately microlensing searches for condensed objects in the foreground of the Magellanic Clouds were flawed by the assumption that the objects would be uniformly (Gaussian) distributed, and because the cadence of daily observations strongly disfavored detection of planet mass microlenses. But quasar microlensing showed them to exist at planetary mass at the same time that a hydro-gravitational theory predicted the planet-mass population as fossils of turbulence at the time of recombination (z = 1100; Gibson 1996, 2001). Where the population has now been detected from MACHO searches to the LMC (Sumi et al. 2011) we compare the quasar microlensing results to the recent determination of the mass distribution function measured for the planetary mass function, and show that the population can account for the baryonic dark matter.